2013
DOI: 10.1093/jac/dkt452
|View full text |Cite
|
Sign up to set email alerts
|

A novel hybrid SCCmec-mecC region in Staphylococcus sciuri

Abstract: ObjectivesMethicillin resistance in Staphylococcus spp. results from the expression of an alternative penicillin-binding protein 2a (encoded by mecA) with a low affinity for β-lactam antibiotics. Recently, a novel variant of mecA known as mecC (formerly mecALGA251) was identified in Staphylococcus aureus isolates from both humans and animals. In this study, we identified two Staphylococcus sciuri subsp. carnaticus isolates from bovine infections that harbour three different mecA homologues: mecA, mecA1 and mec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
75
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(77 citation statements)
references
References 53 publications
2
75
0
Order By: Relevance
“…This mecC gene has also been reported in CoNS as Staphylococcus stepanovicii, Staphylococcus xylosus and Staphylcoccus scirui (Harrison et al, 2013a(Harrison et al, , 2013bLoncaric et al, 2013). As already suggested for the mecA gene, we can probably infer that the origin of the mecC gene is also among the CoNS (Tsubakishita et al, 2010;Couto et al, 2013).…”
Section: Assessment Of Methicillin-resistant Coagulasenegative Staphysupporting
confidence: 70%
“…This mecC gene has also been reported in CoNS as Staphylococcus stepanovicii, Staphylococcus xylosus and Staphylcoccus scirui (Harrison et al, 2013a(Harrison et al, , 2013bLoncaric et al, 2013). As already suggested for the mecA gene, we can probably infer that the origin of the mecC gene is also among the CoNS (Tsubakishita et al, 2010;Couto et al, 2013).…”
Section: Assessment Of Methicillin-resistant Coagulasenegative Staphysupporting
confidence: 70%
“…This appears similar to what is observed for mecA-carrying SCCmec elements in coagulasenegative staphylococci; however, for mecC of course fewer strains are available to date, and the diversity is still difficult to assess. The gene mecC has been detected in Staphylococcus xylosus, S. sciuri, and Staphylococcus stepanovicii [108][109][110]. The mecC allotypes in the S. sciuri and S. xylosus strains are different and are integrated in different SCCmec structures, demonstrating the potential diversity in SCCmec mecC-carrying elements in staphylococci other than S. aureus.…”
Section: Scc Mec Type XI Mecc-carrying Mrsa From Animalsmentioning
confidence: 99%
“…S. sciuri possesses a certain pathogenic potential and is able to induce infections in both, animals (Frey et al, 2013;Dos Santos et al, 2015) and humans (Stepanovic et al, 2003). Some isolates of the S. sciuri group are known to carry different homologues of the methicillin resistance genes mecA, B and C and display methicillin/oxacillin resistance (Becker et al, 2014a,b;Harrison et al, 2014). In the present study, we report the identification of an oxacillin-resistant S. sciuri isolate from a purulent skin lesion of a horse, determined activity of coagulase and hyaluronidase and characterized the antibiotic resistance profile.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, it has been reported that phenotypic methicillin (and other β-lactam) -resistance in Staphylococcaceae members is conferred not only by mecA, but also by different mecA allotypes and also by homologous genes such as mecB and mecC (Becker et al, 2014a,b). Moreover, a hybrid SCCmec consisting of a mecA-encoding SCCmec type VII element and a separate mecC region in terms of a ΨSCCmec element was published for S. sciuri (Harrison et al, 2014;Becker et al, 2014a). These reports might suggest the presence of a further mechomolog or a mec gene hybrid within the genome of the isolated S. sciuri strain, which could not be amplified by the mecA and mecC-specific oligonucleotides.…”
Section: Introductionmentioning
confidence: 99%